Vendettas - Friedel Bolle; Jonathan H. W. Tan; Daniel John Zizzo (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2010)
Vendettas occur in many real world settings where rivals compete for a prize, e.g., winning an election or a competitive promotion, by engaging in retaliatory aggressive behavior. We present a benchmark experiment where two players have an initial probability of winning a prize. Retaliatory vendettas occur and lead agents to the worst possible outcomes in 60% to 80% of cases, counter to self interest predictions, and regardless of whether initial winning probabilities are equal or unequal. Negative emotions are important and interact with economic settings to produce large social inefficiencies. Venting emotions predicts aggression but also reduces it.
Keywords: C72; C91; Z13; 330; trust; income inequality; market; social capital; Spieltheorie; Glücksspiel; Verhaltensökonomik; Vertrauen; Social Capital